Production of Biodiesel from Esterification of Oil Recovered from Palm Oil Mill Effluent (POME) Sludge using Tungstated-Zirconia Composite Catalyst - Hasanudin Hasanudin; Addy Rachmat (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
Solid acid catalyst prepared from tungsten and zirconium oxide composite had been characterized and evaluated on biodiesel production by esterification of low quality oils taken from POME sludge. Catalyst characterization was conducted using Scanning Electron Microscopy (SEM) and acidity test. Acidity test of catalyst resulted using Gravimetry method is 5.4 mole/g. Esterification to produce biodiesel using tungsten and zirconium oxide composite show increasing amount of catalyst used will also increased conversion percentage of biodiesel produced and reach optimum value at 10%. Catalyst:oil ratio used to produce optimum conversion is 8:1 which converted 74.88% oil to biodiesel.Keywords: Tungsten-Zirconia composite, POME Sludge, EsterificationAbstrak (Indonesian). Penelitian tentang preparasi dan karakterisasi katalis komposit tungsten dan zirkonium oksida serta aplikasinya untuk esterifikasi minyak hasil recovery limbah sludge industri kelapa sawit telah dilakukan. Karakterisasi katalis dilakukan dengan menggunakan SEM dan uji sifat keasaman. Sifat keasaman katalis didapat sebesar 5,4 mol/g dengan metode gravimetri. Hasil pembuatan biodiesel dengan menggunakan katalis komposit tungsten dan zirkonium oksida didapatkan bahwa semakin besar jumlah katalis yang digunakan semakin besar pula % konversi biodiesel yang dihasilkan dan optimum pada 10%. Sementara perbandingan jumlah metanol:minyak didapatkan nilai optimum pada perbandingan 8:1 dengan % konversi biodiesel sebesar 74,88%.Kata Kunci: Tungsten-Zirconia composite, POME Sludge, Esterifikasi